Traces of gold : California's natural resources and the claim to realism in western American literature - Witschi, Nicolas S., 1966- (Studies in American literary realism and naturalism., 2002)
Broadening our understanding of what constitutes "realism," Nicolas Witschi artfully demonstrates the linkage of American literary realism to the texts, myths, and resources of the American West. From Gold Rush romances to cowboy Westerns, from hard-boiled detective thrillers to nature writing, the American West has long been known mainly through hackneyed representations in popular genres. But a close look at the literary history of the West reveals a number of writers who claim that their works represent the "real" West. As Nicolas Witschi shows, writers as varied as Bret